Epidemiological investigation of coccidiosis and associated risk factors in broiler chickens immunized with live anticoccidial vaccines in China - Liao, Shenquan; Lin, Xuhui; Zhou, Qingfeng; Wang, Zhanxin; Yan, Zhuanqiang; Wang, Dingai; Su, Guanzhi; Li, Juan; Lv, Minna; Hu, Junjing; Cai, Haiming; Song, Yongle; et al. (Frontiers in Veterinary Science, 2024)
Coccidiosis is a costly intestinal disease of chickens caused by Eimeria species. This infection is associated with high mortality, reduced feed efficiency, and slowed body weight gain. The diagnosis and control of coccidiosis becomes challenging due to the fact that chickens can be infected by seven different Eimeria species and often occur mixed-species co-infections. Grasping the epidemiology of Eimeria species is crucial to estimate the efficiency of poultry management. This study aimed to explore the distribution of Eimeria species in broiler chickens in China after administering live anticoccidial vaccines. A total of 634 samples was obtained, and survey results showed that the prevalence of Eimeria was 86.12% (546/634), and the most common species were E. acervulina (65.62%), E. necatrix (50.95%), E. mitis (50.79%), E. tenella (48.42%) and E. praecox (41.80%). Most samples indicated mixed-species infections (an average of 3.29 species per positive sample). Notably, 63.98% of samples containing 3 to 5 Eimeria species within a single faecal sample. The most prevalent combinations were E. acervulina-E. tenella (38.96%) and E. acervulina-E. necatrix (37.22%). Statistical analysis showed that flocks vaccinated with trivalent vaccines were significant positive for E. necatrix in grower chickens (OR=3.30, p<0.05) compared to starter chickens, and tetravalent vaccinated flocks showed that starter chickens demonstrated a higher susceptibility to E. tenella-E. brunetti (OR=2.03, p<0.05) and E. acervulina-E. maxima (OR=2.05, p<0.05) compared to adult chickens. Geographically, in the case of tetravalent vaccines immunized flocks, a substantial positive association was observed between E. necatrix infection rates and flocks from eastern (OR=3.88, p<0.001), central (OR=2.65, p=0.001), and southern China (OR=3.17, p<0.001) compared to southwestern China. This study also found a positive association between E. necatrix (OR=1.64, 95% CI: 1.07-2.51; p<0.05), E. acervulina (OR=1.59, p<0.05) and E. praecox (OR=1.81, p<0.05) infection and coccidiosis occurrence compared to non-infected flocks in tetravalent vaccinated flocks. This molecular epidemiological investigation showed a high prevalence of Eimeria species in the field. The emergent species, E. brunetti and E. praecox, might be incorporated into the widely-used live vaccines in the future. These insights could be useful in refining coccidiosis control strategies in the poultry industry.